2012
DOI: 10.5851/kosfa.2012.32.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation Efficiency of Escherichia coli and Listeria monocytogenes in Ground Pork by Combination of Natural Food Ingredients and High Pressure Processing

Abstract: The objective of this study was to examine the effects of a combined treatment regarding antimicrobial food ingredients and high pressure processing (HP) on the inactivation efficiency of Escherichia coli and Listeria monocytogenes inoculated into ground pork. Ethanol extracted from garlic, leeks, onions, and ginger powder was prepared. Half of the prepared powder was irradiated at 5 kGy to see the effect of pasteurization before addition. The prepared food ingredients were added into radiation-sterilized grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…acuta inhibited the growth of Salmonella enteritis and Bacillus cereus at concentrations of 4000 and 1000 ppm, respectively ( Kim et al , 2004 ). The antimicrobial activity of plant extracts differs depending on the species and the strain of a pathogen ( El-Chaghaby et al , 2014 ; Jung et al , 2012b ). In addition, extraction solvents affect the antimicrobial and antioxidant activities of plant extracts.…”
Section: Resultsmentioning
confidence: 99%
“…acuta inhibited the growth of Salmonella enteritis and Bacillus cereus at concentrations of 4000 and 1000 ppm, respectively ( Kim et al , 2004 ). The antimicrobial activity of plant extracts differs depending on the species and the strain of a pathogen ( El-Chaghaby et al , 2014 ; Jung et al , 2012b ). In addition, extraction solvents affect the antimicrobial and antioxidant activities of plant extracts.…”
Section: Resultsmentioning
confidence: 99%
“…In meat industry, HPP is commonly used to extend the shelf-life of ready-to-eat meat products. Many studies have been conducted to observe whether HPP gives any impact on functional properties, nutritive values and microbiological quality of the meat and meat products [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Kruk et al . (2011) and Jung et al . (2012) indicated that pressures of 450 to 600 MPa almost completely eliminated three major pathogens, i.e., Salmonella Typhimurium, E. coli , and L. monocytogenes .…”
Section: Resultsmentioning
confidence: 96%
“…The chromosomal DNA of isolated strain was separated by using the SolGent Genomic DNA prep kit (SolGent, Korea). The DNA extracts were used for the polymerase chain reaction (PCR) with the universal primers [27F (5'-AGA GTT TGA TCC TGG CTC AG-3') and 1492R (5'-GGT TAC CTT GTT ACG ACT T-3')] ( Marchesi et al . 1998 ).…”
Section: Methodsmentioning
confidence: 99%